Formation and development of the highest state authorities of the Donetsk People's Republic and the Luhansk People's Republic from self-declaration to admission to the Russian Federation - E. S. Anichkin; I. Yu. Mankovskiy; Yu. I. Kolpakova (Правоприменение)
The subject of this study is a scientific understanding of the formation and development of the supreme state authorities of the People's Republics of Donbass (DPR, LPR) as unrecognized states from the time of their self-declaration in 2014 to their admission to the Russian Federation in 2022.The purpose of the study is to identify the main features, stages of formation and development of institutions of supreme state power (the head of state, parliament, government and courts) in the republics of Donbass in the period from 2014 to 2022.The methodological basis of the research was a wide range of general and special methods of scientific cognition. Dialectical, analysis and synthesis, induction and deduction were used as general scientific methods. Comparative-legal, system-structural and formal-legal methods were used as special methods. General scientific methods, especially dialectical ones, allowed us to study the factors and the process of evolution of the constitutional status of the supreme state authorities of the DPR and LPR in the conditions of military confrontation with the mother state and political rapprochement with Russia. Using the comparative legal method, a comparative analysis of the status of the highest state authorities of the DPR, LPR and the Russian Federation was carried out. The system-structural method was used in the study of intra-system changes in the constitutional status of the studied authorities. With the help of the formal legal method, a study of normative legal sources was conducted, which made it possible to form the logic of the presentation of the material and the conceptual apparatus of the declared topic.The procedure for the formation and activities of the state authorities of the DPR and LPR are regulated by an array of legal acts, the norms of which reflect both the identity of the power institutions of the republics of Donbass and the tendency to the reception of constitutional and legal institutions existing in Russia. This allows us to state with confidence the presence of a number of features in the process of evolution of the highest state authorities of the republics of Donbass, which reflect the focus on integration with a more developed state system of Russia, the formation in a short historical time, the proximity of the mechanism of organization and content of the competence of the highest state authorities of the two republics, caused, including their formation in the conditions of the special the legal regime of martial law.The results of the study can be useful at the present stage of integration of new subjects of the Russian Federation into the legal system of the Russian Federation and into the system of its state authorities.The conclusion is reasoned that the transformation of the institutions of the supreme power of the republics of Donbass has passed two stages and is currently in the third. The first stage is characterized by the formation of its own republican system of supreme state authorities (2014-2018). The second stage is characterized by further improvement and transformation of the status of the supreme state authorities of the republics against the background of increased Russian legal influence (November 2018-2022). The third stage is explained by the adoption of the DPR and the LPR into our state in September 2022 and the beginning of systematic work to change legislation regarding the creation of higher state authorities of new subjects of Russia.